Performance Analysis of the Subak Soka Management Based on Competence, Work Motivation, and Transformational Leadership - Wahyu Indra Sari, I Wayan; Suarmanayasa, I Nengah; Trianasari, Trianasari (International Journal of Management Science and Information Technology, 2000)
The purpose of this study is to empirically prove the influence of competence, work motivation, and transformational leadership on the performance of Subak Soka Tabanan administrators. The novelty of this study lies in the use of modern variables of transformational leadership; competencies applied to traditional Subak organizations. Previous studies generally focus on modern organizations, while empirical research examining this organizational behavior variable in the context of traditional community-based institutions such as Subak is still very limited. In this study, a saturated sample was used, namely all 41 Subak Soka Tabanan administrators. This study employed a quantitative research approach, with data collected through a questionnaire utilizing a five-point Likert scale. To investigate the interrelationships among the variables included in the study, multiple linear regression analysis was conducted with the support of IBM SPSS version 22. The results of the study indicate that partially competence, work motivation, and transformational leadership have a positive and significant influence on the performance of Subak administrators. Simultaneously, the three independent variables have a significant influence on the performance of Subak Soka Tabanan administrators.